Conductivity Measurement of Greywater Using a Microcontroller with Focus on Cost Reduction - Nolkrantz, Jakob (My University, 2018)
To reduce the amount of water that is used every day we must be able to efficiently reuse it. Thus, it becomes important to determine if the water is clean enough for reuse. A part of determining the cleanliness of the water is by measuring its ability to conduct electricity. In this thesis a number of different conductivity probes are presented. A low-cost method for measuring conductivity of greywater was evaluated and implemented. The system is based around an ARM microcontroller and uses a probe that can be manufactured in the same way as a printed circuit board which means that this system can be mass produced at a low cost.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science